2019
DOI: 10.15537/smj.2019.6.24206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic accuracy of smartphone electrocardiogram recorder compared to standard 12 lead electrocardiography in hospital settings

Abstract: Objectives: To evaluate Smartphone-based Electrocardiogram Recorders (S-ECG-R) diagnostic accuracy compared to standard 12 lead ECG. Methods: A cross-sectional comparative study was conducted in a tertiary cardiac center in Riyadh, Kingdom of Saudi Arabia from December 2017 to February 2018. A total of 403 patients underwent both standard 12 leads ECG and S-ECG-R recordings in the same time. All recordings were checked initially by an electrophysiologist to confirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The findings were in consistence with the results of previous studies and demonstrated that both devices had diagnostic accuracies for both regular and irregular beats that were equivalent. [11][12][13][14][15][16][17] These results corroborated Lau et al findings that the S-ECG-R had a 98% sensitivity and 97% specificity. 21 Although the present study encompassed both normal and varied aberrant rhythms, their analysis was restricted to AF.…”
Section: Discussionsupporting
confidence: 81%
“…The findings were in consistence with the results of previous studies and demonstrated that both devices had diagnostic accuracies for both regular and irregular beats that were equivalent. [11][12][13][14][15][16][17] These results corroborated Lau et al findings that the S-ECG-R had a 98% sensitivity and 97% specificity. 21 Although the present study encompassed both normal and varied aberrant rhythms, their analysis was restricted to AF.…”
Section: Discussionsupporting
confidence: 81%